Plastic waste characterisation to maximise landfill diversion from a New Zealand residential construction site - Low, Joanne K.; Hernandez, German; Berry, Terri-Ann (Frontiers in Sustainability, 2024)
In New Zealand, the construction sector is responsible for a large proportion of waste sent to landfill. The plastic profile of construction waste is varied and complex in comparison to other waste types (e.g. timber, concrete, metals, plasterboard). Therefore, the diversion of plastics from landfills is less straightforward, and there are less obvious benefits to recycling this low-density, low-value waste stream. Plastic waste generated by construction activities has not been well-characterised, which has affected opportunities for waste reduction, reuse and recycling. To fill this knowledge gap, this study characterised the plastic waste generated from a residential construction site. This was used to identify opportunities to address the full waste hierarchy through reduction, reuse and recycling and ultimately enable more sustainable plastic waste management.Plastic waste generated from a construction site in Auckland, New Zealand (construction of eight terraced houses) was separated during the project. This was followed by in-depth auditing which further sorted waste types by main composition, followed by analysis for polymer type. The research was phased to determine the plastic waste generated across each of the main construction stages. Once the main polymer types had been identified, local waste providers were contacted to establish opportunities for reuse or recycling. The total mass of plastics generated from all construction stages was 725 kg, 66.4% (by wt.) of which was recycled. Soft plastics, predominantly low-density polyethylene, were the most common plastic type; this was followed by pipes and expanded polystyrene. Plastic packaging, primarily soft plastics and polystyrene, accounted for 60% of total plastics and were mostly generated in the final stages of construction (i.e. fittings and fit-out). This characterisation of construction plastic waste can be used to demonstrate the feasibility of sustainable plastic waste management in Auckland and to identify construction plastic waste sources on an international scale. More studies on a variety of construction types (e.g. detached residential, apartment blocks, commercial) are required to address the full breadth of plastic materials used and to drive a more circular economy for this potential resource.